Identifikasi Faktor-Faktor Penentu Pendapatan UMKM Potensial dan Telaah Kebijakan Untuk Peningkatannya - Yuvanda, Sesraria; Oktarina, Elsa; Ardhana, Kevin; Azra, Jessica (ARBITRASE: Journal of Economics and Accounting, 2025)
During the global crisis, MSMEs have proven to be capable of growing and developing even in difficult times. MSMEs have also been able to overcome the decline in employment and business opportunities by shifting to independent enterprises. Although MSMEs hold a very important position in the national economy, their business operations do not always run smoothly due to various obstacles and challenges faced by MSME actors. One of the common problems in MSMEs is the lack of understanding of the factors that influence the income of potential MSMEs in Jambi City. The aim of this research is to identify the factors that affect the income of potential MSMEs in Jambi City. The respondents in this study are 50 potential MSMEs in Jambi City, based on data from the Jambi City Office of Manpower and MSMEs, IPEMI, and Bank Indonesia. The data collected were processed and analyzed using multiple linear regression analysis. The results show that the variables of capital, labor, technology, and production value have a significant effect on the income of potential MSMEs in Jambi City, while the variables of business duration and training do not have a significant effect on the income of potential MSMEs in Jambi City."